Quercetin attenuates deoxynivalenol-induced intestinal barrier dysfunction by activation of Nrf2 signaling pathway in IPEC-J2 cells and weaned piglets - Enkai Li; Chuang Li; Nathan Horn; Kolapo M. Ajuwon (Current Research in Toxicology, 2023)
The presence of deoxynivalenol (DON), one of the most frequently occurring mycotoxin, in food and feed has been considered a risk factor to both human and animal health. Molecular mechanisms that regulate DON effects in tissues are still poorly understood. However, recent evidence suggests that nuclear factor erythroid 2-like 2 (Nrf2) may be a major target during mycotoxin-induced intestinal barrier dysfunction. Although quercetin, a plant-derived flavonoid, is known to induce the activation of Nrf2 signaling pathway, its potential to mitigate effects of DON and the implication of Nrf2 in its physiological effects is poorly understood. Therefore, this study was conducted to investigate the protective effects of quercetin in alleviating the DON-induced barrier loss and intestinal injuries in IPEC-J2 cells and weaned piglets and determine the potential role of Nrf2. Quercetin treatment dose-dependently increased mRNA expression of Nrf2 target gene, NQO-1, and concomitantly increased the expression of claudin-4 at both mRNA and protein levels. Quercetin supplementation also reversed the reduction of claudin-4 caused by DON exposure in vivo and in vitro. The decreased membrane presence of claudin-4 and ZO-1 induced by DON was also blocked by quercetin. Furthermore, quercetin attenuated the endocytosis and degradation of claudin-4 caused by DON exposure. The effects of quercetin also included the restoration of transepithelial electrical resistance (TEER) and reduction of FITC-dextran permeability that have been perturbed by DON. However, the protective effects of quercetin against DON exposure were abolished by a specific Nrf2 inhibitor (brusatol), confirming the importance of Nrf2 in the regulation of TJP expression and barrier function by quercetin. In vivo study in weaned pigs showed that DON exposure impaired villus-crypt morphology as indicated by diffuse apical villus necrosis, villus atrophy and fusion. Notably, intestinal injuries caused by DON administration were partly mitigated by quercetin supplementation. Collectively, this study shows that quercetin could be used to prevent the DON-induced gut barrier dysfunction in humans and animals and the protective effects of quercetin against DON-induced intestinal barrier disruption is partly through Nrf2-dependent signaling pathway.